ANALISIS EKONOMI DIGITAL DAN KETERBUKAAN TERHADAP PERTUMBUHAN GDP NEGARA ASEAN - Wibowo, Edi Wahyu (JURNAL LENTERA BISNIS, 2018)
AbstractThe ASEAN Economic Community was formed with the aim of achieving the perfection of economic integration in the ASEAN region which is believed to provide tangible benefits to all elements of society. Opportunities of digital economy and the pollination of each ASEAN country is very important to succeed the purpose of the establishment of The ASEAN Economic Community. This study uses quantitative methods with secondary data by panel period 2012-2016 by combining 10 ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, Philippines, Vietnam, Myanmar, Brunei, Laos, Cambodia). T test results obtained are the effect of digital variables on the GDP of ASEAN countries ie the probability value of t-statistics obtained 0.0420. Then the statistical probability <α = 5% is 0.0420 <0.05. So it can be concluded that digital variables partially have a positive significance to GDP variables. While the influence of openness to GDP growth of ASEAN countries is the probability value of t-statistics obtained 0.6386, then the statistical probability <α = 5% is 0.6386> 0.005. So it can be concluded that the variables of disclosure partially no effect on the significance of GDP variables. While the simultaneous F test result is the effect of digital variables and openness to GDP growth of ASEAN countries obtained Adjustted R-Squere value of 0.994. This shows that the model is able to explain 99.4% of the dependent variable, while the remaining 0.52 other factors influenced beyond the regression model. Digital influence on GDP growth of ASEAN countries is good so it needs to be improved to manage internet users. Internet users are expected not only as a consumer but also create business opportunities to make a star up (entrepreneur) for economic growth in each country can be improved. While the influence of openness to the growth of GDP of ASEAN countries needs to be improved especially in producing products that can be exported and reduce the import of goods, export and import tariff are also to be re-arranged so that grow export climate in each country. It is expected that openness will increase so much investment will be present so that ultimately the purpose of establishment of ASEAN Economic Community can prosper each ASEAN country.Keywords: Digital Economy, Openness, GDP, ASEAN